Evaluasi Kesiapan Infrastruktur Dasar Sekolah untuk Mendukung Program Lingkungan Hidup Berbasis Adiwiyata - Siska Rahmawati; Chade Chatena Munthe; Catherine Elisabeth Sinaga; Berliana Afriani Manurung; Fakhrunnisa Rosdianti; Muhammad Ikhlas (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to comprehensively evaluate the readiness of basic school infrastructure to support the implementation of the Adiwiyata Program at SDN 101771, with a focus on the development of environmentally friendly schools and environmental education. This study collected data using a qualitative descriptive method by conducting in-depth interviews with the Principal, observing school activities and infrastructure directly. The results of the study indicate that the basic infrastructure of SDN 101771 is still in the development stage and several significant challenges have been encountered. One of the main obstacles is the limited environmental facilities, such as inadequate trash bins and little green space outside. More intensive education and training are also needed to address students' low environmental awareness. To improve the success of the Adiwiyata program, school management plays an important role in planning, managing, and collaborating with external parties. Active participation of all students, strong support from the government, and the sustainability of this program are very important. Therefore, this study provides suggestions for improving school infrastructure, increasing public awareness of the environment, and increasing collaboration between schools and related parties.